Extended technology acceptance model to explain the mechanism of modular construction adoption - Shin, Jiwoong; Moon, Sungwoo; Cho, Bong ho; Hwang, Sungjoo; Choi, Byungjoo (Journal of Cleaner Production, 2022)
Introduction: While it is highly expected that modular construction can overcome the limitations of conventional construction methods, modular construction use in the field is currently insufficient. Previous studies have attempted to analyze what hinders the use of modular technology and find alternative solutions, but most studies have limitations in that it is difficult to explain the mechanisms of users' modular technology adoption in detail. Thus, the purpose of this study is to investigate the mechanisms of modular construction adoption using a technology acceptance model to overcome previous studies’ limitations. Method: Empirical survey data from 208 construction experts were collected to test research hypotheses in the research model of modular construction adoption. The collected data were analyzed using a two-step approach (i.e., CFA, SEM). Results: It was found that Outcome Expectation (OE), Institutional Barrier (IB), and Private Interests (PI) affected Attitude (ATT) and Behavioral Intention (BI) with the users’ Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) acting as mediating variables. Among these, PI was found to have the greatest impact on technology adoption and IB had a negative impact on both PU and ATT, indicating an urgent need for improvements in public policies relating to current modular construction use. Applications: The results of this study permit a detailed explanation of the modular construction adoption mechanism. Furthermore, the results can provide practical assistance and advice when developing various measures for stimulating the use of modular construction technology.
Keywords: Extended technology acceptance models; Institutional barriers; Modular construction adoption; Modulars; Outcome expectation; Perceived usefulness; Private interest; Structural equation models; Technology acceptance model; Technology adoption; Institutional barrier; Modular construction; Modular construction adoption; Outcome expectation; Private interests; Structural equation modeling; Technology acceptance model